Fentanyl Preference among People Who Inject Drugs in West Virginia. (3rd August 2020) - Mazhnaya, Alyona; O'Rourke, Allison; White, Rebecca Hamilton; Park, Ju Nyeong; Kilkenny, Michael E.; Sherman, Susan G.; Allen, Sean T.
Abstract: Background: Overdose fatality rates in rural areas surpass those in urban areas with the state of West Virginia (WV) reporting the highest drug overdose death rate in 2017. There is a gap in understanding fentanyl preference among rural people who inject drugs (PWID). The aim of this study is to investigate factors associated with fentanyl preference among rural PWID in WV. Methods: This analysis uses data from a PWID population estimation study conducted in Cabell County, WV in June-July 2018. Factors associated with fentanyl preference were assessed using multivariable Poisson regression with a robust variance estimate. Results: Among PWID who reported having ever used fentanyl ( n = 311), 43.4% reported preferring drugs containing fentanyl. Participants reported high levels of socioeconomic vulnerability, including homelessness (57.9%) and food insecurity (66.9%). Recent increases in drug use and injecting more than one drug in the past 6 months were reported by 27.0% and 84.2% of participants, respectively. In adjusted analyses, fentanyl preference was associated with being younger (PrR:0.98, 95% CI: 0.97-1.00), being female (PrR:1.45, 95% CI:1.14-1.83), being a Cabell county resident (PrR:0.60, 95% CI: 0.45-0.81), increased drug use in the past 6 months (PrR:1.28, 95% CI: 1.01-1.63), and injecting fentanyl in the past 6 months (PrR:1.89, 95% CI: 1.29-2.75). Conclusion: Fentanyl preference is highly prevalent among rural PWID in WV and associated with factors that may exacerbate overdose risks. There is an urgent need for increased access to tailored harm reduction services that address risks associated with fentanyl preference.